Mechanobiology of collective cell behaviours - Ladoux, Benoit; Mège, René Marc (Nature Reviews Molecular Cell Biology, 2017)
The way in which cells coordinate their behaviours during various biological processes, including morphogenesis, cancer progression and tissue remodelling, largely depends on the mechanical properties of the external environment. In contrast to single cells, collective cell behaviours rely on the cellular interactions not only with the surrounding extracellular matrix but also with neighbouring cells. Collective dynamics is not simply the result of many individually moving blocks. Instead, cells coordinate their movements by actively interacting with each other. These mechanisms are governed by mechanosensitive adhesion complexes at the cell-substrate interface and cell-cell junctions, which respond to but also further transmit physical signals. The mechanosensitivity and mechanotransduction at adhesion complexes are important for regulating tissue cohesiveness and thus are important for collective cell behaviours. Recent studies have shown that the physical properties of the cellular environment, which include matrix stiffness, topography, geometry and the application of external forces, can alter collective cell behaviours, tissue organization and cell-generated forces. On the basis of these findings, we can now start building our understanding of the mechanobiology of collective cell movements that span over multiple length scales from the molecular to the tissue level.
CRIS-Team Scopus Importer:2024-02-19